Loss of platelet-derived growth factor-stimulated phospholipase activity in NIH-3T3 cells expressing the EJ-ras oncogene. - Benjamin, C W (1987)
Data indicating that the 21-kDa protein (p21) Harvey-ras gene product shares sequence homology with guanine nucleotide-binding proteins (G proteins) has stimulated research on the influence(s) of p21 on G-protein-regulated systems in vertebrate cells. Our previous work demonstrated that NIH-3T3 mouse cells expressing high levels of the cellular ras oncogene isolated from the EJ human bladder carcinoma (EJ-ras) exhibited reduced hormone-stimulated adenylate cyclase activity. We now report that in these cells another enzyme system thought to be regulated by G proteins is inhibited, namely phospholipases A2 and C. NIH-3T3 cells incubated in plasma-derived serum release significant levels of prostaglandin E2 (PGE2) as determined by radioimmunoassay when exposed to platelet-derived growth factor (PDGF) at 2 units/ml; the levels of PGE2 released from EJ-ras-transfected cells are only 3% those of controls despite a similar basal (unstimulated) release from control and EJ-ras-transfected cells. The lack of PDGF-stimulated PGE2 release from EJ-ras-transfected cells is not due to a defect in the prostaglandin cyclooxygenase enzyme, since incubation of control cells and EJ-ras-transfected cells in 0.33, 3.3, or 33 microM arachidonate resulted in identical levels of PGE2 release. The lack of PDGF-stimulated PGE2 release from EJ-ras-transfected cells also does not result from the loss of functional PDGF receptors. EJ-ras-transformed cells bind 70% as much 125I-labeled PDGF as control cells and are stimulated to incorporate [3H]thymidine and to proliferate after exposure to PDGF. Moreover, this inhibition is not likely the result of a secondary cellular effect related to the transformed phenotype, since NIH-3T3 cells transformed by v-src released PGE2 at wild-type levels after exposure to PDGF. Determination of total water-soluble inositolphospholipids and changes in the specific activities of phosphatidylcholine in control and EJ-ras-transfected cells demonstrated that PDGF-stimulated phospholipase C and A2 activities are inhibited in the EJ-ras-transfected cells.